Hungarian Monitoring, 9 September 1990 . [Magyar rádiófigyelő], 1990. szeptember 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Helsinki summit - Anti-government protest in Brasov Domestic Affairs: - Parties hold election rallies - Géza Szőcs is the general secretary of the Democratic Alliance of Hungarians in Romania (RMDSZ) - Soviet troop withdrawals from Tolna county - Shootings on the Austrian-Hungarian border Külpolitika: - Helsinki csúcs - Kormányellenes tüntetés Brassóban Belpolitika: - Választási nagygyűléseket tartanak a pártok - Szőcs Géza az RMDSZ főtitkára - Szovjet csapatkivonás Tolna megyéből - Lövések az osztrák-magyar határon